Combined Stereotactic Body Radiotherapy and Immunotherapy Versus Transarterial Chemoembolization in Locally Advanced Hepatocellular Carcinoma: A Propensity Score Matching Analysis - Chiang, Chi-Leung; Chiu, Keith Wan-Hang; Lee, Francis Ann-Shing; Kong, Feng-Ming Spring; Chan, Albert Chi-Yan (Frontiers in Oncology, 2021)
Immunotherapy has achieved modest clinical activity in HCC patients. Propensity score matching analysis was conducted to compare the efficacy and safety of combined stereotactic SBRT-IO versus TACE in patients with locally advanced HCC in a tertiary centre of Hong Kong. Patients with locally advanced HCC who were medically inoperable for, refractory to, or refused to curative surgical interventions were eligible. The primary outcome was PFS; the secondary outcomes were OS, ORR as per mRECIST version 1.1, and TRAEs. Matching pair analysis was performed to compare the clinical outcomes. A total of 226 patients were eligible. 16 patients in the SBRT-IO group were matched with 48 patients treated with TACE. The median tumour size was 10 cm (range: 2.9-19.6 cm) and 20.3% of the patients had portal vein invasion. The 12-month and 24-month PFS were significantly better in the SBRT-IO group (93.3% vs 16.7% and 77.8% vs 2.1%, respectively, p<0.001); the 12-month and 24-month OS were also better in the SBRT-IO arm (93.8% vs 31.3% and 80.4% vs 8.3%, respectively, p<0.001). The ORR was 87.5% (CR: 50%, PR: 37.5%) in SBRT-IO arm compared to 16.7% (CR: 2.4%, PR: 14.3%) in those receiving TACE alone (p<0.001). There were fewer ≥ grade 3 TRAE (60.4% vs 18.8%, p=0.004) and treatment discontinuations (25% vs 12.5%, p=0.295) due to adverse events in the SBRT-IO arm. SBRT-IO had significant superior survival and less treatment toxicity than TACE in patients with locally advanced HCC. Our results provide rationale for studying this combination therapy in prospective randomised trials.